Respuesta :

Hello there!

8x = 2y + 5
3x = y + 7
Use the substitution property
We need to solve 3x = y + 7 for y
3x = y + 7
3x - y = 7
-y = 7 - 3x
Divide both sides by -1
-y/-1 = -3x -7/-1
y = 3x - 7
Substitute 3x - 7 for y in 8x = 2y + 5
8x = 2y + 5
8x = 2(3x - 7) + 5
8x = 6x - 14 + 5
8x = 6x - 9
8x - 6x = -9
2x = -9
x= -9/2
To find y, we need to substitute -9/2 for x in y = 3x -7
y = 3x - 7
y = 3(-9/2) - 7
y = -41/2

The correct answer is option A (-9/2; -41/2)

Good luck with your studies!
ACCESS MORE